Innovative Peptide Bioconjugation Chemistry with Radionuclides: Beyond Classical Click Chemistry - Samantha Leier; Frank Wuest (MDPI AG, 2024)
Background: The incorporation of radionuclides into peptides and larger biomolecules requires efficient and sometimes biorthogonal reaction conditions, to which click chemistry provides a convenient approach. Methods: Traditionally, click-based radiolabeling techniques have focused on classical click chemistry, such as copper(I)-catalyzed alkyne-azide [3+2] cycloaddition (CuAAC), strain-promoted azide-alkyne [3+2] cycloaddition (SPAAC), traceless Staudinger ligation, and inverse electron demand Diels-Alder (IEDDA). Results: However, newly emerging click-based radiolabeling techniques, including tyrosine-click, sulfo-click, sulfur(VI) fluoride exchange (SuFEx), thiol-ene click, azo coupling, hydrazone formations, oxime formations, and RIKEN click offer valuable alternatives to classical click chemistry. Conclusions: This review will discuss the applications of these techniques in peptide radiochemistry.